Public sector housing law - Hughes, David (Butterworths, 2000)
This acclaimed textbook is ideal for all those seeking a comprehensive overview of the duties and powers of authorities and associations as providers and allocators of housing. It offers clear and authoritative guidance through the dense mass of intertwined statutory provisions and case law decisions which make this a complex area of the law